2022
DOI: 10.3390/molecules27196306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Silver Nanoparticles from Rhizophora apiculata and Studies on Their Wound Healing, Antioxidant, Anti-Inflammatory, and Cytotoxic Activity

Abstract: Silver nanoparticles (AgNPs) have recently gained interest in the medical field because of their biological features. The present study aimed at screening Rhizophora apiculata secondary metabolites, quantifying their flavonoids and total phenolics content, green synthesis and characterization of R. apiculata silver nanoparticles. In addition, an assessment of in vitro cytotoxic, antioxidant, anti-inflammatory and wound healing activity of R. apiculata and its synthesized AgNPs was carried out. The powdered pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 71 publications
2
14
0
1
Order By: Relevance
“…The fact that the peak absorption of all the samples remained at around 440 nm is helpful for the methodology, as it allows to determine the result of the reaction making only one spectrophotometric measurement in spite of obtaining whole UV-Vis spectra. The wavelength of peak absorption at 410-460 nm is characteristic for silver nanoparticles [19,23,24], and at 425-440 nm is characteristic for silver nanoparticles synthesised using Artemisia plant extracts [36,60,61,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the peak absorption of all the samples remained at around 440 nm is helpful for the methodology, as it allows to determine the result of the reaction making only one spectrophotometric measurement in spite of obtaining whole UV-Vis spectra. The wavelength of peak absorption at 410-460 nm is characteristic for silver nanoparticles [19,23,24], and at 425-440 nm is characteristic for silver nanoparticles synthesised using Artemisia plant extracts [36,60,61,64].…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining AgNPs is of interest not only as a method and assessment of the level of reducing power, but also as an independent biotechnological process of creating a product (nanoparticles), which can find wide practical applications due to having anticancer effect, antibacterial, antioxidant, anti-inflammatory and anti-hyperglycemic activity [18][19][20][21][22][23][24][25], as well as anti-quorum sensing potential [26]. Advances of such "green" silver, zink, gold, platinum, nickel, aluminum and iron nanoparticles are widely researched [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…After 10 min, the absorbance of the reaction mixture was taken at 230 nm using a blank solution (phosphate buffer and hydrogen peroxide free). The absorbance was taken in triplicate . Percentage inhibition was calculated by using eq .…”
Section: Methodsmentioning
confidence: 99%
“…AgNPs demonstrated stronger cell migration and percentage of wound closure (82.79%) compared to the plant extract (75.23%). 15 Recently, unique nanostructures and nanomaterials have been created thanks to a technique called electron beam (EB) irradiation. In general, the potent reducing species produced by radiolysis make ionizing radiation more effective for the synthesis of AgNPs than nonionizing radiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, the cell viability assay revealed that the AgNPs were less toxic (IC 50 105.5 μg/mL) compared to the R. apiculata extract (IC 50 47.47 μg/mL) against the noncancerous fibroblast L929 cell line. AgNPs demonstrated stronger cell migration and percentage of wound closure (82.79%) compared to the plant extract (75.23%) …”
Section: Introductionmentioning
confidence: 99%